Effect of Degree of Substitution and Molecular Weight on Transfection Efficacy of Starch-Based siRNA Delivery System - Amir Regev; Chen Benafsha; Riki Goldbart; Tamar Traitel; Moshe Elkabets; Joseph Kost (Polysaccharides)
RNA interference (RNAi) is a promising approach for gene therapy in cancers, but it requires carriers to protect and deliver therapeutic small interfering RNA (siRNA) molecules to cancerous cells. Starch-based carriers, such as quaternized starch (Q-Starch), have been shown to be biocompatible and are able to form nanocomplexes with siRNA, but significant electrostatic interactions between the carrier and siRNA prevent its release at the target site. In this study, we aim to characterize the effects of the degree of substitution (DS) and molecular weight (Mw) of Q-Starch on the gene silencing capabilities of the Q-Starch/siRNA transfection system. We show that reducing the DS reduces the electrostatic interactions between Q-Starch and siRNA, which now decomplex at more physiologically relevant conditions, but also affects additional parameters such as complex size while mostly maintaining cellular uptake capabilities. Notably, reducing the DS renders Q-Starch more susceptible to enzymatic degradation by α-amylase during the initial Q-Starch pretreatment. Enzymatic cleavage leads to a reduction in the Mw of Q-Starch, resulting in a 25% enhancement in its transfection capabilities. This study provides a better understanding of the effects of the DS and Mw on the polysaccharide-based siRNA delivery system and indicates that the polysaccharide Mw may be the key factor in determining the transfection efficacy of this system.